2011
DOI: 10.1038/nature10433
|View full text |Cite
|
Sign up to set email alerts
|

Strong contributors to network persistence are the most vulnerable to extinction

Abstract: The architecture of mutualistic networks facilitates coexistence of individual participants by minimizing competition relative to facilitation. However, it is not known whether this benefit is received by each participant node in proportion to its overall contribution to network persistence. This issue is critical to understanding the trade-offs faced by individual nodes in a network. We address this question by applying a suite of structural and dynamic methods to an ensemble of flowering plant/insect pollina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
344
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(373 citation statements)
references
References 22 publications
15
344
1
4
Order By: Relevance
“…We used the nestedness contribution (the difference in the degree of nestedness of the total allele × site matrix and a matrix where a certain site has been excluded; Saavedra et al. 2011) as measured by the NODF metric (nestedness from overlap and decreasing fill; Almeida‐Neto et al. 2008) to infer the role of each site in the decline of allele diversity.…”
Section: Methodsmentioning
confidence: 99%
“…We used the nestedness contribution (the difference in the degree of nestedness of the total allele × site matrix and a matrix where a certain site has been excluded; Saavedra et al. 2011) as measured by the NODF metric (nestedness from overlap and decreasing fill; Almeida‐Neto et al. 2008) to infer the role of each site in the decline of allele diversity.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamical models are also being used to explore primary and secondary species extinctions [72,73]. The position of species in a network has been used to estimate their dynamic importance [27] and vulnerability to extinction [74]. In an applied context, food-web studies have now been used to determine future vulnerability to species loss.…”
Section: Emerging Trends and Future Directionsmentioning
confidence: 99%
“…The concept was first proposed in the early twentieth century but only became popular among ecologists with its application to the biogeographic pattern of species occurrence in islands and other fragmented landscapes 1,2 . More recently, nestedness in species interaction networks has received significant attention [3][4][5][6][7] , where it has been suggested that a nested pattern of interactions leads to greater biodiversity in mutualistic systems such as plant-pollinator networks 8,9 . In a nested bipartite network or graph, interactions are organized such that specialists (for example, pollinators that visit few plants) interact with subsets of the species with whom generalists (for example, pollinators that visit many plants) interact.…”
mentioning
confidence: 99%